It is daylight / Arda Collins ; foreword by Louise Glück. - Collins, Arda, 1974- (Yale series of younger poets, 2009)
Arda Collins is the 2008 winner of the annual Yale Series of Younger Poets competition. Mesmerizing and electric, her poems seem to be articulatedin the privacy of an enclosed space. The poems are concrete and yet metaphysically challenging, both witty and despairing. Collins' emotional complexity and uncommon range make this debut both thrillingly imaginative and ethical in its uncompromising attention to detail. In her Foreword, contest judge Louise Glück observes, "I know no poet whose sense of fraud, the inflated emptiness that substitutes for feeling, is more acute." Glück calls Collins' volume "savage, desolate, brutally ironic ... a book of astonishing originality and intensity, unprecedented, unrepeatable."